Demineralization study of Indian Assam coking coal by sodium hydroxide leaching - Kumar M.; Gupta R.C. (My University, 2025)
The purpose of this study was to examine the ash removal efficiency of sodium hydroxide leaching from Assam coking coal so that it could be used for the manufacture of graphite electrodes. The parameters tested were sodium hydroxide concentration, particle size of coal, NaOH solution / coal ratio, leaching temperature and time, and heat treatment of coal. Increase in NaOH concentration up to 500 gL-1 was found to increase the extent of ash removal. The ash content of the leached coal decreased with decrease in particle size, but very finely ground I-72 mesh) particles reduced the ash removal rate. Increase in leaching temperature (50-120°) and time (30-180 min) considerably reduced the ash content of the leached coal Heat-treated (at 1300°C) coal (i.e., coke) has much lower ash removal efficiency than raw coal.